Features of the course of primary and recurrent herpetic keratitis developing following COVID-19 vaccination (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To assess the features of the course of primary and recurrent herpetic keratitis (HK) developing following COVID-19 vaccination.Material and Methods: Medical records of 31 patients (34 eyes) with post-COVID-19 vaccination HK were reviewed. The patients were divided into two post-COVID-19 vaccination HK groups: group 1 with primary HK (9 patients; 9 eyes) and group 2 with recurrent HK (22 patients; 25 eyes). Levels of total vitamin D, and immunoglobulin G (IgG) antibodies against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike receptor-binding domain (S-RBD), herpes simplex virus (HSV)-1/2, cytomegalovirus (CMV) and Epstein-Barr nuclear antigen (EBNA) were assessed in venous serum.Results: The median time (interquartile range (IQR)) from COVID-19 vaccination to the development of keratitis was 15 days (10-30) for patients with primary HK and 7 days (4-10) for patients with recurrent HK. The level of vitamin D in venous serum was lower than normal in 84.2% of the total sample of patients. Of the eyes that developed primary HK following COVID-19 vaccination, 3 (33.3%) had dendritic HK and 6 (66.7%) had non-necrotizing stromal HK. Of the eyes that developed recurrent HK following COVID-19 vaccination, 2 (8%) had dendritic HK, 21 (81%) had non-necrotizing stromal HK and 2 (6%) had ulcerative necrotizing HK.Conclusion: Non-necrotizing stromal HK was the most common form of post COVID-19 vaccination HK in both groups. The level of vitamin D in venous serum was lower than normal in 84.2% of post COVID-19 vaccination patients with HK. Levels of anti-HSV IgG, anti-EBNA IgG, anti-VZV IgG, and anti-CMV IgG antibodies in venous serum exceeded normal ranges in 86.5%, 96.4%, 92%, and 88.8%, respectively, of post COVID-19 vaccination patients with HK.
Keywords: COVID-19; herpetic keratitis; recurrent herpetic keratitis; herpes virus; cornea; vaccine